Organizational and technical peculiarities of presenting for identification - Pomazanov, Vitaliy Viktorovich; Gritsaev, Sergei Ivanovich; Stepanenko, Sergei Grigorevich (Полицейская и следственная деятельность, 2021)
The research object is social relations connected with the legal regulation, organization and the tactics of identification. The authors consider the types of identification mentioned in the criminal procedure law, and those used during criminal investigation. Having compared their volume and contents, the authors note that the number of types of identification used in the work of law-enforcement bodies is larger than that of those formalized in the Criminal procedure Law of the Russian Federation. This situation doesn't violate the law, since such types of identification as the identification of animals, territories, etc. are the components (subtypes) of the types of identification formalized in the law. The authors study the correlation between the organization and tactics of presenting for identification and attempt to systematize the investigator's actions during the preparation and organization of various types of presenting for identification. The scientific novelty of the research consists in the formation of tactical techniques of presenting for identification through the lens of registration and correlation of subjects of the forensic tactics (the most rational ways of organizing an investigation - the problem scope) and the organization of criminal investigation (the creation of a structure of the investigative activities, the conditions for its effective implementation, and the investigation management - the organizational and administrative scope). This approach helps to create a detailed list of tactical recommendations for the organization, preparation and realization of various types of presenting for identification with account for the specificity of the object of identification, and their classification in accordance with the stages of this investigation.